Selection of facade's alternatives of commercial and public buildings based on multiple criteria - Šaparauskas, Jonas; Zavadskas, Edmundas Kazimieras; Turskis, Zenonas (International Journal of Strategic Property Management, 2011)
An appropriate mechanism for supporting design management practices at an early stage of project is crucial in terms of adding value over scope, time and total investment strategic decisions. The clients are not only interested in value for money in relation to the investment in project development but costs associated in operation and maintenance over project life cycle as well. These criteria make possible to evaluate design solutions which can be characterized by quantitative and qualitative criteria which possibly have different weight, dimension and direction of optimization (maximisation or minimization). The purpose of this article – is to compare different designs of building or its structure and to select the best alternative using criteria of optimality. Case study is demonstrated by selecting the best facade system to cover the building. For this purpose four alternatives of building facades are under consideration. Two criteria (out of three) indicate that for the case study the most preferable facade‘s alternative is gas silicate masonry, covered by Rockwool and “Minerit” facade plates.First Publish Online: 4 Jul 2011